The pyroptosis-related gene signature predicts prognosis and indicates the immune microenvironment status of chronic lymphocytic leukemia - Sha, Yeqin; Jiang, Rui; Miao, Yi; Qin, Shuchao; Wu, Wei; Xia, Yi; Wang, Li; Fan, Lei; Jin, Hui; Xu, Wei; Li, Jianyong; Zhu, Huayuan (Frontiers in Immunology, 2022)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in Western world with great heterogeneity. Pyroptosis has been recently recognized as an inflammatory form of programmed cell death (PCD) and shares close relationship with apoptosis. Although the role of apoptosis in CLL was comprehensively studied and successfully applied in clinical treatment, the relationship between pyroptosis genes and CLL remained largely unknown. In this study, 8 differentially expressed pyroptosis-related genes (PRGs) were identified between CLL and normal B cells. In order to screen out the prognostic value of differentially expressed PRGs, univariate and multivariate Cox regression analysis were conducted and a risk model with 3-PRGs signatures (GSDME, NLRP3 and PLCG1) was constructed. All CLL samples were stratified into high- and low-risk subgroups according to risk scores. Risk model showed high efficacy in predicting both overall survival (OS) and time to first treatment (TTFT). Gene ontology (GO), Kyoto Encyclopaedia of Genes and Genomes (KEGG) and Gene Set Enrichment Analysis (GSEA) showed the dysregulation of immune and inflammatory response in high-risk group. Simple sample GSEA (ssGSEA) analysis of immune cells infiltration and activity of immune-related pathways also displayed decreased antitumor immunity in high-risk group. In conclusion, PRGs genes are of prognostic value in CLL and may play important roles in tumor immunity, the underlying relationship between PRGs and CLL needs to be explored further.